Effects of cassava genotype, climate, and the Bemisia tabaci vector population on the development of African cassava mosaic geminivirus (ACMV) - Abdullahi, I.; Atiri, G.I.; Dixon, Alfred G.O.; Winter, S.; Thottappilly, G. (Akademiai Kiado Zrt., 2003)
A survey was carried out in the 1996/97 and 1997/98 growing seasons on a field planted in three replicates with five clones of cassava at the International Institute of Tropical Agriculture, Ibadan, located in a transition forest, to determine the effects of cassava genotype and climate on the development of African cassava mosaic geminivirus (ACMV) and changes in the Bemisia tabaci population. Cassava genotype, climate and their interactions have significant